Deaths during Sexual Activity - Okulevičiūtė, Agnė; Chmieliauskas, Sigitas; Laima, Sigitas; Vasiljevaitė, Diana; Stasiūnienė, Jurgita (Acta medica Lituanica, 2024)
Background: Deaths during sexual activities are a rarely identified phenomenon in forensic medicine practice. Most often, such deaths are classified as accidents or deaths due to the manifestation of certain diseases during sexual activity. It is important to rule out homicide or suicide as the cause of death when investigating sexual deaths. Determining the cause of death requires a comprehensive assessment of the evidence and circumstances and should not be based solely on autopsy findings. When determining the cause of death, it is necessary to evaluate the circumstances of the discovery, important evidence found near the body, the position of the deceased, the place where the deceased was found, and the characteristics of the environment. Cases: Case 1: A 65-year-old male was clothed in women’s underwear and was found hanging in a noose in a bedroom after a house fire. The autopsy revealed a ligature mark on the neck, bruises in neck muscles, tears in carotid arteries, and signs of acute pulmonary distension. The cause of death was determined to be suffocation due to neck compression by a ligature, compounded by significant alcohol intoxication, with additional postmortem burns covering 30% of the body surface area likely occurring after death. Case 2: A 55-year-old naked male was found without external injuries but with a plastic tube inserted into the rectum, causing a 2.5 cm rupture in the ileum. The perforation led to complications, including purulent diffuse peritonitis, intoxication, and acute cardiac and respiratory failure, resulting in death within 3-6 hours after insertion. Concurrent findings included atherosclerotic changes in the heart, internal organ hyperemia and edema, hepatic steatosis, renal cyst, and a lack of ethyl alcohol in blood but 0.17 ‰ presence in urine according to toxicology analysis. Conclusions: A detailed evaluation of all the evidence is very important in the forensic examination of the deceased during sexual activity. Therefore, to determine the cause of death, not only the autopsy data, toxicological and microscopic examinations of the deceased are important, but also the evaluation of all findings at the scene. The most common cause of death of an autoerotic nature is asphyxia, and the most commonly identified group of the dead are men aged around 40 years.